Physical health outcomes and implementation of behavioural health homes: a comprehensive review. (2nd November 2018) - Murphy, Karly A.; Daumit, Gail L.; Stone, Elizabeth; McGinty, Emma E.
Abstract: People with serious mental illness (SMI) have mortality rates 2–3-times higher than the general population, mostly driven by physical health conditions. Behavioural health homes (BHHs) integrate primary care into specialty mental healthcare settings with the goal of improving management of physical health conditions among people with SMI. Implementation and evaluation of BHH models is increasing in the US. This comprehensive review summarized the available evidence on the effects of BHHs on physical healthcare delivery and outcomes and identified perceived barriers and facilitators that have arisen during implementation to-date. This review found 11 studies reporting outcomes data on utilization, screening/monitoring, health promotion, patient-reported outcomes, physical health and/or costs of BHHs. The results of the review suggest that BHHs have resulted in improved primary care access and screening and monitoring for cardiovascular-related conditions among consumers with SMI. No significant effect of BHHs was reported for outcomes on diabetes control, weight management, or smoking cessation. Overall, the physical health outcomes data is limited and mixed, and implementation of BHHs is variable.